Regulation of a Cytochrome P450 Gene CYP94B1 by WRKY33 Transcription Factor Controls Apoplastic Barrier Formation in Roots to Confer Salt Tolerance - Krishnamurthy, Pannaga; Vishal, Bhushan; Ho, Wan Jing; Lok, Felicia Chien Joo; Lee, Felicia Si Min; Kumar, Prakash P (Plant physiology (Bethesda), 2020)
Salinity is an environmental stress that causes decline in crop yield. and other mangroves have adaptations such as ultrafiltration at the roots aided by apoplastic cell wall barriers to thrive in saline conditions. We studied a cytochrome P450 gene from , , and its putative ortholog in Arabidopsis ( ), , which are involved in apoplastic barrier formation. Both genes were induced by 30 min of salt treatment in the roots. Heterologous expression of in the Arabidopsis mutant and wild-type rice ( ) conferred increased NaCl tolerance to seedlings by enhancing root suberin deposition. Histochemical staining and gas chromatography-tandem mass spectrometry quantification of suberin precursors confirmed the role of CYP94B1 in suberin biosynthesis. Using chromatin immunoprecipitation and yeast one-hybrid and luciferase assays, we identified AtWRKY33 as the upstream regulator of in Arabidopsis. In addition, mutants exhibited reduced suberin and salt-sensitive phenotypes, which were rescued by expressing in the background. This further confirmed that AtWRKY33-mediated regulation of is part of the salt tolerance mechanism. Our findings may help efforts aimed at generating salt-tolerant crops.